To what extent can a South African resident donor's offshore investment trust be arranged so as to avoid the following South African taxes and duty - May, Carl (Department of Commercial Law, 2023)
This report will deal with a situation of the donor, commonly known as the settlor donating assets by way of an agreement to independent trustee/s located offshore for the benefit of various agreed beneficiaries; some, or more of them, being South African residents. The report will also examine the ramifications for a South African donor and beneficiary from an income tax, capital gains tax, donations tax and estate duty point of view that will exclude a consideration of value added tax and regional services council levies on the basis that the offshore trusts being considered here, are not business or trading trusts in most instances. The report will examine planning opportunities and the attendant risks of legal challenge currently presenting themselves.